Utilizing Cognitive Illustration as a Kanji Memorization Strategy in Kanji Learning - Sutedi, Dedi; Juangsih, Juju (Universitas Pendidikan Indonesia (Indonesia University of Education), 2024)
The study reports on the effect of ‘Cognitive Illustration’ in Kanji learning in the JFL setting. Cognitive illustration is not a formal concept that can be found regularly in Kanji teaching and learning methods. It is purposely used in this study to describe ‘kinds of imagery that students have when they see or hear a Kanji character and its meaning by referring to its formation process, including pictographs (shoukei moji), simple ideographs (shiji moji), compound ideographs (kai-i moji), and phonetic-ideographic characters (keisei moji)’. Involving twenty-eight students taking a Kanji course, namely fifteen students participated in the experimental class and thirteen students participated in the control class, this experimental research observes the effect of cognitive illustration on students who learn hundreds and fifteen Kanji of Japanese Language Proficiency Test (JLPT) N5 or basic level. The results show that students in the experimental class perform better in Kanji memorization than those in the control groups. It can be seen from the t-test results with the t-score value obtained (11,38) which is much higher than the t-table, both at the 5% (2,06) and 1% (2,78) significance levels. In relation to Kanji learning, there are some factors that contribute to the enhancement of Kanji learning, including varying Kanji learning strategies, thorough guided instruction, and ordering Kanji strategies.